1912
DOI: 10.2307/1778326
|View full text |Cite
|
Sign up to set email alerts
|

Miss Semple on the Influences of Geographical Environment

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In retrospect, this critique of the Westphalian model of territorial sovereignty, which still remains dominant today, anticipated the material turn in territorial theorization a century later (Clark and Jones 2017; Peters et al, 2018; Squire, 2016). However, although some deemed it the most notable work published in English on the ‘influence of natural conditions on human history’ (Chisholm, 1912: 31), it was widely criticized as simplistic and sweeping by leading social scientists, disregarded as an example of a discipline overreaching itself (Koelsch, 2014). Most problematically, environmental determinism, which Semple introduced to mainstream geography via Ratzel’s work, was already falling out of favour by the second decade of the 20th century.…”
Section: From Determinism To Idealismmentioning
confidence: 99%
“…In retrospect, this critique of the Westphalian model of territorial sovereignty, which still remains dominant today, anticipated the material turn in territorial theorization a century later (Clark and Jones 2017; Peters et al, 2018; Squire, 2016). However, although some deemed it the most notable work published in English on the ‘influence of natural conditions on human history’ (Chisholm, 1912: 31), it was widely criticized as simplistic and sweeping by leading social scientists, disregarded as an example of a discipline overreaching itself (Koelsch, 2014). Most problematically, environmental determinism, which Semple introduced to mainstream geography via Ratzel’s work, was already falling out of favour by the second decade of the 20th century.…”
Section: From Determinism To Idealismmentioning
confidence: 99%
“…Chisholm's perspective on Influences was rehearsed and expanded in his review of the book, published in The Geographical Journal (Chisholm 1912). In earlier correspondence, John Scott Keltie had assured Semple of a ‘stunning review .…”
Section: The Reception Of Influences In the United Kingdommentioning
confidence: 99%
“…Chisholm found fault in Semple's adaptation of Ratzel, especially her over‐reliance on the first volume of his Anthropogeographie . Aspects of Ratzel's second volume, particularly its discussion of ‘the structural works of men’, Chisholm argued, might have been incorporated usefully into Semple's analysis (Chisholm 1912, 32). This criticism was slight, and Chisholm concluded that ‘one cannot be too emphatic in expressing the value of this work’ (1912, 32).…”
Section: The Reception Of Influences In the United Kingdommentioning
confidence: 99%
See 1 more Smart Citation
“…For Markham, Close's address was ‘perfectly astounding’, and ‘must be challenged’. George Goudie Chisholm, lecturer in geography at Edinburgh, rebutted Close by pointing in his teaching to Ellen Churchill Semple's 1911 work (Chisholm 1912). J W Gregory, then a geologist at the university of Glasgow and who taught geography there, offered a placatory interpretation in noting that ‘I thought all Close meant was that cartography is the primary duty of geography’ and that he [Gregory]‘did not think it [Close's address] would have the slightest effect on the British Association or on the development of geography in this country’.…”
Section: Geography a Science? Close's 1911‘geographical Heresy’mentioning
confidence: 99%